Deity from a Python, Earth from a Hen, Humankind from Mystery: Narrative and Knowledge in Yorùbá Cosmology - Harvey, Marcus Louis (Estudos de religião, 2015)
Yoruba cosmology Represents a significant gap in Yoruba studies. Unfortunately, originary narratives Within this cosmology trend not to be Explicitly investigated at the level of epistemology. The concerns methodology, phenomenological studies of Yoruba cosmology are rare and Typically gain less traction than studies produced using preponderant social scientific approaches. In this essay, Entitled "Deity from the Python Earth from the Hen, Humankind from Mystery: Narrative and Knowledge in Yoruba Cosmology, "I argue que the phenomenological analysis of originary narratives in Yoruba cosmology illumines the presence of orienting concepts . que articulate the Yoruba epistemological perspective We find in some of these narratives five orienting concepts que convey this perspective: mystery, relationality materially-based, unpredictability, the permanency of existential conflict, and irresolution.